2017
DOI: 10.1021/acsbiomaterials.6b00500
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nerve Guidance Conduit-Based Therapeutics for Peripheral Nerve Repair

Abstract: Peripheral nerve injuries have high incidence rates, limited treatment options and poor clinical outcomes, rendering a significant socioeconomic burden. For effective peripheral nerve repair, the gap or site of injury must be structurally bridged to promote correct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 165 publications
0
92
0
Order By: Relevance
“…Nerve-guide-conduits or nerve-guidance-channels (NGCs) are 3D constructs for whole nerve therapies in vivo (Anderson et al, 2017;Lackington et al, 2017). They are currently used as implants for neural repair in humans.…”
Section: Topographical Cues Drive Alignment and Directionalitymentioning
confidence: 99%
“…Nerve-guide-conduits or nerve-guidance-channels (NGCs) are 3D constructs for whole nerve therapies in vivo (Anderson et al, 2017;Lackington et al, 2017). They are currently used as implants for neural repair in humans.…”
Section: Topographical Cues Drive Alignment and Directionalitymentioning
confidence: 99%
“…In addition, microscale topographical cues that mimic the peripheral nerve bundle can significantly affect the microcellular environment such as alignment, extension of axons, and dendrites. [7,9,[12][13][14][15] In our previous studies, we have performed various experiments using topographical cues to mimic target tissues appropriately, and we confirmed that groove-ridge pattern can significantly improve cell migration and differentiation. [16][17][18][19] We have found that topographical substrate could enhance neurite outgrowth and alignment by using various sizes of poly(lactic-co-glycolic acid) (PLGA) topographical substrates.…”
Section: Introductionmentioning
confidence: 73%
“…Among FDA‐approved NGCs, filled and hollowed NGCs are already commercially available, such as NeuraGen 3D (Integra LifeScience) and Neurolac (Polyganics Inc.). These NGCs can induce different results of nerve regeneration depending on animal model, nerve gap, and defect size . Some research studies have reported that NGCs filled with inner filler in lumen can serve as guidance channel to enhance axonal regeneration compared to hollow NGCs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations